Neuropsychological assessment of aggressive offenders: a Delphi consensus study - Hutten, Juliette C.; van Horn, Joan E.; Hoppenbrouwers, Sylco S.; Ziermans, Tim B.; Geurts, Hilde M.; , The Forensic Neuropsychology Consortium; Al-Taiar, Hasanen; Bolognini, Nadia; Breuer, Lisanne; Dongen, Josanne van; Garmoe, William; Griffor, Beverly; et al. (Frontiers in Psychology, 2024)
Objective: This study explores the intricate relationship between cognitive functioning and aggression, with a specific focus on individuals prone to reactive or proactive aggression. The purpose of the study was to identify important neuropsychological constructs and suitable tests for comprehending and addressing aggression.Methods: An international panel of 32 forensic neuropsychology experts participated in this threeround Delphi study consisting of iterative online questionnaires. The experts rated the importance of constructs based on the Research Domain Criteria (RDoC) framework. Subsequently, they suggested tests that can be used to assess these constructs and rated their suitability. Results: The panel identified the RDoC domains Negative Valence Systems, Social Processes, Cognitive Systems and Positive Valence Systems as most important in understanding aggression. Notably, the results underscore the significance of Positive Valence Systems in proactive aggression and Negative Valence Systems in reactive aggression. The panel suggested a diverse array of 223 different tests, although they noted that not every RDoC construct can be effectively measured through a neuropsychological test. The added value of a multimodal assessment strategy is discussed.Conclusions: This research advances our understanding of the RDoC constructs related to aggression and provides valuable insights for assessment strategies. Rather than suggesting a fixed set of tests, our study takes a flexible approach by presenting a top-3 list for each construct. This approach allows for tailored assessment to meet specific clinical or research needs. An important limitation is the predominantly Dutch composition of the expert panel, despite extensive efforts to diversify. * These constructs are not part of the RDoC, but were suggested as additions in round 1.